Test driven development contribution in universities in producing quality software: a systematic review - Yahya, Norzariyah; Awang Abu Bakar, Normi Sham (IEEE, 2014)
Test driven development (TDD) is one of Agile techniques adopted in education. TDD is an ideal approach to be taught in university due to its capability in producing quality software and at the same time teaching novice programmer to test and develop a product simultaneously. It helps novice programmer to think before they develop rather than using “trial-and-error” approach in their project. However, based on the existing research, TDD contribution in producing a better quality and the perception among novice programmers towards it need to be analized. This systematic review will identify the quality of a product produced by the students in university and also their perception towards TDD.